Exploring Indigenous Ways of Coping After a Wildfire Disaster in Northern Alberta, Canada. (July 2021) - Montesanti, Stephanie; Fitzpatrick, Kayla; Azimi, Tara; McGee, Tara; Fayant, Bryan; Albert, Lorraine
In May 2016, a wildfire devastated a northern region of Alberta, Canada, resulting in negative consequences on physical and mental stress, social relationships, and overall resilience among Indigenous residents. Research on coping and managing stress following a disaster has failed to incorporate unique characteristics from Indigenous perspectives. Sharing circles were held in urban and rural community settings to capture: (a) Indigenous perspectives of coping, (b) individual and collective strengths that helped Indigenous residents and communities to cope during and after the wildfire, and (c) intergenerational experiences of coping from stress among Indigenous residents. Indigenous residents' experience with coping from the wildfire was shaped by: (a) heightened physical and emotional stress, (b) existing structural inequities, and (c) strong community cohesion and connection to culture. An unexpected outcome of this research was the therapeutic value of the sharing circles for participants to share their experience.